Trunk Shaker Mechanical Harvesting Systems - Stephen H. Futch; Fritz M. Roka (EDIS)
As discussed in other documents regarding various aspects of mechanical harvesting, Florida citrus growers must adopt new technology to reduce harvesting costs, thus allowing our citrus industry to compete with low-wage countries in a global juice marketplace. Trunk shake systems are a viable mechanical harvesting system which growers should consider in an effort to lower harvesting costs, increase fruit returns, and remain competitive. This document is HS1005, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published March 2005.